PROMINENT UKRAINIAN SCIENTIST VOLODYMYR BETZ AND HIS CONTRIBUTION TO THE DEVELOPMENT OF NEUROANATOMY - A. V. Kovalchuk; L. A. Cherkasova; A. J. Yanchyshyn (Bogomolets National Medical University, 2015)
Summary: The history of Ukrainian science is rich in the names of people who were able to significantly accelerate its progress and contribute to significant achievements. One of them was Vladimir Alekseevich Betz - Professor, Head of the Department of Anatomy of the Kiev Imperial University of St. Vladimir for 22 years (1868-1890). During the period of his scientific activity at the university, VA Betz wrote many works, however, his most significant discovery was related to the study of the structure of the central nervous system. The giant pyramidal cells he discovered in the 5th layer of the cerebral cortex, also known as Betz cells, clarified the anatomy and physiology, the most complex and at the same time interesting system of the human body, and became the impetus for the further development of the world and modern neuroanatomy in particular. Today, there is no textbook in the world of anatomy, histology, physiology, or neurology that does not describe these cells. For his discovery VA Betz was awarded many prizes and medals, received repeated offers to sell his collection of drugs, which he made himself. However, Vladimir Alekseevich Betz, as a devoted patriot of his country, presented all the materials to the Department of Human Anatomy, where he worked all his life. This article reflects the main milestones in the life of the scientist, as well as the discovery of giant pyramidal cells.